2021
DOI: 10.1038/s41397-021-00245-5
|View full text |Cite
|
Sign up to set email alerts
|

New genetic variants associated with major adverse cardiovascular events in patients with acute coronary syndromes and treated with clopidogrel and aspirin

Abstract: Although a few studies have reported the effects of several polymorphisms on major adverse cardiovascular events (MACE) in patients with acute coronary syndromes (ACS) and those undergoing percutaneous coronary intervention (PCI), these genotypes account for only a small fraction of the variation and evidence is insufficient. This study aims to identify new genetic variants associated with MACE end point during the 18-month follow-up period by a two-stage large-scale sequencing data, including high-depth whole… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Therefore, MYOM2 may be important for hypertrophic cardiomyopathy and Tetralogy of Fallot [28]. MYOM2 is downregulated in both animal models and patients with phenotypes related to major adverse cardiovascular events [29]. The inhibitory function of another miR-483-5p gene target revealed by our analysis is TIMP2, a key determinant of post-MI myocardial remodeling; TIMP2 replenishment in diseased myocardium could provide a potential therapy in reducing or preventing disease progression [30].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Therefore, MYOM2 may be important for hypertrophic cardiomyopathy and Tetralogy of Fallot [28]. MYOM2 is downregulated in both animal models and patients with phenotypes related to major adverse cardiovascular events [29]. The inhibitory function of another miR-483-5p gene target revealed by our analysis is TIMP2, a key determinant of post-MI myocardial remodeling; TIMP2 replenishment in diseased myocardium could provide a potential therapy in reducing or preventing disease progression [30].…”
Section: Discussionmentioning
confidence: 78%
“…In the present study, we specify the candidate target genes for mir-483-5p in heart tissue, among them PLA2G5, GRK2, MYOM2, TIMP2, ADAMTS2 and HGSNAT. Indeed, regulation of many of these genes related to cardiovascular diseases and correlated with MI in previously published reports [26][27][28][29][30][31] (Scheme 2). For instance, elevated plasma sPLA2-IIA (encoded by the PLA2G5 gene) predicts coronary heart disease risk [26] and is involved in inflammation.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, MYOM2 was also defined as a pleiotropic gene of CAD and T2DM by MTAR ( P MTAR-O ), with 11 novel pleiotropic SNPs discovered in the vicinity of this gene. Previous GWASs have found that other SNPs (rs755900673 and rs17064642) at this gene were associated with T2DM and adverse cardiovascular events, and the novel pleiotropic SNPs we identified provide more evidence for the shared mechanism between these two diseases [ 41 , 42 ]. MYOM2 encodes a major component of the vertebrate myofibrillar M band, and hypomethylated CpG sites of MYOM2 have previously been reported to be associated with atherosclerosis-related phenotypes [ 43 ].…”
Section: Discussionmentioning
confidence: 79%
“…We identified 50 of these genetic variants significantly associated with the severity of CVDs (e.g., ACS, CAD, and/or PAD). These variants ( Table 3 ) were associated with inflammatory pathways, cholesterol transport, and regulation and signaling cascades in previous GWASs [ 38 , 50 , 51 ]. Although most of these CVD-linked variants occur within intronic regions, they can either enhance or reduce gene expressions [ 52 ].…”
Section: Discussionmentioning
confidence: 95%
“…Reports of numerous SNPs associated with CVDs can be found in the available literature [ 38 , 50 , 51 ]. We identified 50 of these genetic variants significantly associated with the severity of CVDs (e.g., ACS, CAD, and/or PAD).…”
Section: Discussionmentioning
confidence: 99%